1. y=x³/3+2*sinxy`=3x²/3+2*cosxy`=x²+2*cosx (B).2. f``(4)=(√x+x+1)`=(x¹/²)`+x`+1`=1/(2√x)+1=1/(2*√4)+1=1+1/4=1¹/₄ (Б)3. y`=(x⁷-4/x⁶)`=7x⁶-(4*x⁻⁶)`=7x⁶-(4*(-6)*x⁻⁷=7x⁶+24/x⁷ (Г).4. y`(1)=((3-x²)(x²+6))`=-2x*(x²+6)+(3-x²)*2x=-2x³-12x+6x-2x³=-4x³-6x=-10 (Г)5. S`(3)=(t²+10t-7)`=2t+10=-2*3+10=4 (Г).6. f(x)=-x²-4x+2 x₀=-1yk=f(x₀)+f`(x₀(x-x₀)f(-1)=-(-1)²-4(-1)+2=-1+4+2=5.f`(-1)=(-x²-4x+2)`=-2x-4=-2*(-1)-4=2-4=-2 ⇒yk=5-2(x-(-1)=5-2x-2=-2x+3 (B).7. y=3x-x³y`=3-3x²3(1-x²)>01-x²>0x²-1<0(x+1)(x-1)<0-∞_____+_____-1_____-______1______+_____+∞ ⇒x∈(-1;1) (A).8. f`(x)=(-x³/3+x²/2+2x-3)`=0-x²+x+2=0 |×(-1)x²-x-2=0 D=9x₁=2 x₂=-1 (A).